GROWTH AND HARVEST YIELD OF VEGETABLES WITH FISH CULTIVATION IN BUCKETS (BUDIKDAMBER) SYSTEM - Sumiasih, Inanpi Hidayati; Yodfiatfinda, .; Yana, Dewi Canda (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2024)
The continuous construction of buildings and roads in Jakarta has led to increasingly limited land conditions, resulting in minimal opportunities for farming and animal husbandry. One way to cultivate vegetables and raise fish in limited land is through the bucket fish farming system. This study aims to obtain good planting media for optimal growth and harvest results in vegetable and fish cultivation in buckets. The research was conducted at the Universitas Trilogi greenhouse from April to June 2021, using planting media types (Cocopeat and ash) and vegetable types (lettuce and mustard greens). The results on lettuce with Cocopeat planting media, with parameters including plant height, number of leaves, total weight, and fresh weight, showed better values compared to ash planting media, with respective values of 33.53 cm, 9 leaves, 25.81 grams, and 20.74 grams. The results on mustard greens with Cocopeat planting media, with parameters including plant height, number of leaves, total weight, fresh weight, and leaf color chart, showed better values compared to using ash planting media, with respective values of 23.07 cm, 5 leaves, 19.34 grams, 12.09 grams, and 3.63. The weight of catfish planted with vegetables using ash planting media on lettuce and mustard greens had higher weight values compared to using Cocopeat planting media.